Bankruptcy law and practice in malaysia, and its relevance to tax claims - Das, V. (2010)

(untitled)
This paper nakes a modest attempt to give an outline of bankruptcy and its application in Malaysia. The aim is to provide a general concept of bankruptcy law and its implications on per~n and property concerned. The Act is designed in line with the English Statute with modifications to suit local con~ext. There seems to be a general tendency to dismiss bankruptcy as the end of the road because of its limitations and psychological effect but on critical observation it will be seen that it is not the case if the principles are understood in conjunction with the law. There is always a light at the end of the tunnel. The dissertation is submitted with respect more on an informative vein as to enable the public and private sectors to know the rudiments of bankruptcy law and its effect on the society and the individuals alike. In the first part, bankruptcy practice is shown with comprehensive insight into its application and effect while in the second, its relevance to tax claims is briefly discussed. The author ventures to hope that the study would help the subject to be understood in its true spectrum.